2014
DOI: 10.3233/bmr-130431
|View full text |Cite
|
Sign up to set email alerts
|

Inter and intra-rater reliability of mobile device goniometer in measuring lumbar flexion range of motion

Abstract: Mobile device goniometer has high intra-rater reliability. The inter-rater reliability was moderate. This device can be used to assess range of motion of spine flexion, representing uni-planar movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
17
0
11
Order By: Relevance
“…The electrogoniometer had its intrarater reproducibility tested in two studies, which showed excellent results 39,43 , and excellent concurrent validity when compared to the inclinometer 39,42 . Another type of goniometer that presented excellent results was the mobile device goniometer (iPod), with correlations above 0.8 for both intra-and inter-rater reproducibility and concurrent validity 40 , supporting the agreement between the measures taken by different raters and at different times. Gravity goniometers and the parallelogram also presented excellent intra-rater reproducibility 21 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The electrogoniometer had its intrarater reproducibility tested in two studies, which showed excellent results 39,43 , and excellent concurrent validity when compared to the inclinometer 39,42 . Another type of goniometer that presented excellent results was the mobile device goniometer (iPod), with correlations above 0.8 for both intra-and inter-rater reproducibility and concurrent validity 40 , supporting the agreement between the measures taken by different raters and at different times. Gravity goniometers and the parallelogram also presented excellent intra-rater reproducibility 21 .…”
Section: Discussionmentioning
confidence: 87%
“…However, when we take into account the meta-analysis results (APPENDIX), a high methodological heterogeneity between studies is evidenced, which prevents assertions and extrapolations about metric measurements of intra-rater reproducibility, requiring new studies, in addition to the fact that analysis was only possible with the use of Pearson's r-related information. A good reason to use dual inclinometers is that they are recommended by the American Medical Association (AMA), in the Guides to the Evaluation of Permanent Impaiment 40,65 . However, inclinometers presented concurrent validity tested only with the same instrument, which limits knowledge about the true value obtained, besides being relatively expensive, difficult to handle and may contain marking and assembling errors; therefore, it is necessary to master this technique in order to obtain precise measures 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Bedekar et al utilized only one measurement and calculated the reported angle measurement on assumed constant femur/tibia length ratios; this paper also reported the results of using an application which the authors developed. [3] This evaluation of smartphone based measurements relied on the inherent accelerometer function available on most smartphones and was not influenced by outside programming or mathematical estimation.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Recent smartphone technology, however, has led to the development of accelerometer-based applications that have the potential to be used for measuring ROM. [3] As a clinical tool for measuring ROM, the accuracy, intraobserver, and interobserver reliability has not been established compared to radiographic assessments. Furthermore, no standard exists for the use or positioning of the smartphone when obtaining measurements.…”
Section: Introductionmentioning
confidence: 99%